The Influence of Zakat Knowledge, Religiosity and Income on Zakat Paying Compliance (Case Study of UPZ Disdukcapil Ciamis Regency) - Rahmi Maolia; Nila Nurochani; Eris Munandar (QISTINA: Jurnal Multidisiplin Indonesia, 2022)
This study aims to determine the effect of zakat knowledge, religiosity and income on zakat paying compliance at UPZ Disdukcapil, Ciamis Regency. This study uses quantitative research methods using primary data with data collection techniques through distributing questionnaires and data analysis using multiple linear regression. The results of this study indicate that the results of the t-test variable knowledge partially have a positive and not significant effect on compliance with paying zakat (Y) at UPZ Disdukcapil, the results of tcount 1,824 and ttable 1,696 mean that tcount ttable with a significance of 0.997 0.05, the results of the t-test for the variable religiosity partially has a positive and significant effect on compliance with paying zakat results of tcount 3,074 and ttable 1,696 meaning tcount ttable with a significance of 0.004 0.05 and the results of the t test income variable partially have a positive and not significant effect on compliance with paying zakat (Y) at UPZ Disdukcapil the results of tcount 1,709 and ttable 1,696 mean tcount ttable with a significance of 0.142 0.05. While the F test obtained Fcount of 7,615 and Ftable of 2.92 meaning Fcount Ftable so the variables of knowledge, religiosity and income simultaneously have a positive and significant effect on compliance with paying zakat.